Generic imatinib in the treatment of chronic myeloid leukemia: two years’ experience in latvia - Lejniece, S.; Udre, I.; Rivkina, A. (Experimental Oncology, 2017)
Background: Imatinib is tyrosine kinase inhibitor (TKI) and as a targeted anti-cancer agent has significantly changed chronic myeloid leukemia (CML) prognosis and patient survival. Currently TKI is the main therapy in CML Philadelphia chromosome-positive (Ph-positive) cases. When generics of imatinib appeared in the pharmaceuticals market, reimbursement policies in many countries switched to using generics or encouraged use of generic imatinib to lower the expenses. Cost savings were substantial; however, for doctors and CML patients the efficacy, safety and quality of generic imatinib were an issue of concern. Objective: Since the global number of CML patients, who in the future will have to switch from original imatinib to generic imatinib, is high, the aim of study was to monitor, whether during 24 months of generic imatinib usage patients maintain the achieved major molecular response (MMR) or whether the treatment results are inferior. Methods: We conducted a retrospective study, which included CML patients, who were above 18 years of age and who until May 2013 had used at least for 2 years (24 months) the original imatinib, and following that used at least for 24 months one of the generic imatinib medicines. In 2013, before switching to generic imatinib, all patients had reached MMR in accordance with European LeukemiaNet (ELN) Guidelines. Every three months blood count, BCR-ABL fusion gene (BCR-ABL), biochemical analysis and side effect were monitored. Results: Our study proved that CML patients, who had achieved MMR by original imatinib therapy, retained MMR during 24 months of generic imatinib therapy. Nobody was switched to second line generation TKI. During observation period neither haematological, nor non-hematological toxicity was found. Conclusion: Our study proved that CML patients, who had achieved MMR by original imatinib therapy, retained MMR during 24 months of generic imatinib therapy. This demonstrates that generic imatinib is not inferior to original imatinib. As to expenses, the annual costs of generic imatinib are lower by 96%, which is a significant benefit to health-care financing.